Democracia Digital Popular: articulações discursivas nos dispostivos de participação cidadã Participa.br e Decide Madrid - Gomes, Romulo Fernando Lemos (2019)
This research analyzes the discursive articulations from two experiments of citizenship collaboration in digital ambiences: Participa.br, designed by the Brazilian government, and Decide Madrid, created by Madrid City Hall. The objective is to investigate the meanings of democracy produced by both enunciators. These platforms were launched as post-event agencements of the Brazilian uprisings, occurred in June 2013, and the 15M, in Madrid context. For this reason, I initially attempted to understand the sociopolitical contexts in which both dispositives emerged. In the sequence, I described the methodologies of participation adopted by the enunciators, as well as the plasticity of these platforms in the digital environment. In this sense, the established meanings were evidenced into syncretic systems (visual/verbal), and the relational aspects were enabled by Web 2.0 tools. For the empirical verification and better understanding of the operative inner rules of these dispositives, I selected textual corpus based on two Participation Tracks from Participa.br: ―1ª Conferência Virtual da Comigrar‖ and ―Consulta sobre regulamentação da Lei 13.445/17 (Lei de Migração)‖. From Decide Madrid, I collected declarations from the citizen proposal "Arborización masiva en Madrid" and from the project presented to the 2016 participatory budget ―Nueva red de puntos limpios‖. The theoretical framework was based on the demodiversity matrixes and post-abyssal democracy, written by Boaventura de Sousa Santos and José Manuel Mendes (2017). Also, it was based on the radical and plural democracy project, developed by Ernesto Laclau and Chantal Mouffe (2015), in dialogue with Laclau's (2013) perspectives about Mouffe's (2015) chains of equivalence and formation of collective identities, that discusses the concept of the political and Jacques Rancière (1996) in his concept of disagreement as a foundational category of politics. The analysis of the interaction and meaning regimes were based on Landowski (2014), besides the Social Network Analysis (ARS) metrics (RECUERO et al., 2015) and supported by Gephi data visualization software. The analyses demonstrated how institutional enunciators interact with citizen-users and these with other participants, shedding light upon the articulating demands in chains of equivalence processes and, consequently, upon the popular collective identities formation in democratic practices mediated by digital. I hypothesize that there is a communicational dimension, marked by various interaction regimes, constitutive of the historical subject of democracy, the people. In the digital dispositives of political participation, this communicative condition is more evident because they, themselves, are composed of technological apparatuses dedicated to mediation. However, it is insufficient to build channels between state-society having in mind that interactions are only among isolated groups of individuals. The proposal of a popular digital democracy wants to rescue the interactional centrality between collective identities in political processes, especially for decision-making purposes